Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/cncr.24735
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the blood brain barrier by brain metastases of triple‐negative and basal‐type breast cancer but not HER2/neu‐positive breast cancer

Abstract: BACKGROUND: Generally, the blood-brain barrier (BBB) of brain metastasis was thought to be disrupted. METHODS: We retrospectively performed immunohistochemical staining for glucose transporter 1 (GLUT1) and breast cancer resistance protein (BCRP) to evaluate the status of the BBB in resected brain metastases. Associations between expression of GLUT1 and/or BCRP and the immunohistochemical profiles of breast cancers, such as the statuses of hormone receptors, human epidermal growth factor receptor 2 (HER2/neu),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 25 publications
2
97
1
3
Order By: Relevance
“…In our study, the immunohistochemical profiles for ER, PR and HER2 differed between the primary tumors and the brain metastases in 29.3% of the patients. Prior hormone therapy or chemotherapy exerted an effect on this discordance phenomenon (1)(2)(3)(4)(5)32,33). All the patients with ER or PR alterations (positive-negative and negative-positive) had received hormone therapy prior to the development of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the immunohistochemical profiles for ER, PR and HER2 differed between the primary tumors and the brain metastases in 29.3% of the patients. Prior hormone therapy or chemotherapy exerted an effect on this discordance phenomenon (1)(2)(3)(4)(5)32,33). All the patients with ER or PR alterations (positive-negative and negative-positive) had received hormone therapy prior to the development of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of the blood-brain barrier, with efflux pumps in brain endothelium capable of preventing the penetration of many therapeutic agents (especially natural products such as anthracyclines and taxanes), has long been recognized, but also debated as a cause of therapeutic failure, given its disruption in the setting of brain metastasis (9). One recent clinical report has suggested that disruption of the blood-brain barrier is common in triple-negative breast cancers but rare in HER2-positive brain metastases (10).…”
mentioning
confidence: 99%
“…Little is known about the pharmacokinetics of trastuzumab in the CNS and its ability to pass the intact BBB [8]. Stemmler and colleagues measured trastuzumab levels in the serum and in CSF of HER2+ MBC patients with brain metastases and systemic trastuzumab treatment, before and after WBRT.…”
Section: Discussionmentioning
confidence: 99%
“…HER2+ breast cancer has an increased risk of central nervous system (CNS) metastases [2] but there are little data on LC frequency in these tumors [3]. Trastuzumab, a monoclonal antibody against the extracellular domain of the HER2 receptor, is highly effective in systemic control of HER2+ metastatic breast cancer [4] but it is not clear if it can penetrate the intact blood brain barrier (BBB) [5]. We report the case of a patient who received weekly intrathecal (IT) trastuzumab for LC from HER2+ breast cancer for 18 months, with impressive neurological benefit.…”
Section: Introductionmentioning
confidence: 99%